Innovative Anti-Inflammatory and Pro-resolving Strategies for Pulmonary Hypertension: High Blood Pressure Research Council of Australia Award 2019. Issue 5 (27th September 2021) - Scott, Tara E.; Qin, Cheng Xue; Drummond, Grant R.; Hobbs, Adrian J.; Kemp-Harper, Barbara K.
Abstract : Pulmonary hypertension is a rare, ostensibly incurable, and etiologically diverse disease with an unacceptably high 5-year mortality rate (≈50%), worse than many cancers. Irrespective of pathogenic origin, dysregulated immune processes underlie pulmonary hypertension pathobiology, particularly pertaining to pulmonary vascular remodeling. As such, a variety of proinflammatory pathways have been mooted as novel therapeutic targets. One such pathway involves the family of innate immune regulators known as inflammasomes. In addition, a new and emerging concept is differentiating between anti-inflammatory approaches versus those that promote pro-resolving pathways. This review will briefly introduce inflammasomes and examine recent literature concerning their role in pulmonary hypertension. Moreover, it will explore the difference between inflammation-suppressing and pro-resolution approaches and how this links to inflammasomes. Finally, we will investigate new avenues for targeting inflammation in pulmonary hypertension via more targeted anti-inflammatory or inflammation resolving strategies.